Beyond nutrients, health effects of entomophagy: a systematic review. Issue 1 (11th February 2019) - Ayensu, Jessica; Annan, Reginald Adjetey; Edusei, Anthony; Lutterodt, Herman
Abstract : Purpose: Edible insects have emerged as a promising inexpensive option to address malnutrition among vulnerable groups in the world. However, it is not clear whether including insects in diets can improve health outcomes. This paper aimed to investigate the impact of edible insect consumption on human health. Design/methodology/approach: A search was conducted in PubMed Central, BioMed Central, Plosone, Cochrane, Google Scholar, Google Search and bibliographies for all human studies on the impact of edible insect consumption on human health published from January 1990 to April 2018. Findings: Twelve studies met the inclusion criteria. Consumption of cereals fortified with edible insects improved iron status and growth in infants and led to the development of life threatening anaphylactic reactions in sensitive people. Practical implications: Edible insects are nutritious. More rigorous studies are needed to confirm nutrient bioavailability, acceptability and nutritional benefits in humans. Originality/value: This review shows that the utilization of edible insects as food promotes desirable health outcomes, but caution must be taken to prevent allergic reactions in some cases.